Somos nós que fazemos a vida como der, ou puder, ou quiser: beleza e construção do corpo em narrativas biográficas de mulheres - Ponte, Vanessa Paula (2008)
This study has a focus in the interpretation of narratives of women of Fortaleza (capital of the Ceará State) that practice gymnastics and their experiences with physical appearance in the quotidian, work, home and in the various social interactions. Starting by these narratives, I want to offer a possible comprehension about how those women, which belong to different social, economical and cultural realities, live with their own bodies, the feelings that break out, and mainly, in how these life experiences reveal aspects of the social context that we are in. Many are the stimulus and demands of mainstream society for women achieve certain esthetical pattern: the processes of socialization, the established “beauty market” and the mass media. This research shows, therefore, how those women build, since the early ages, relationships with their bodies under this current ideals of beauty.